The Mormon Trail (South Fork) - Geary County Historical Society; The Church of Jesus Christ of Latter-day Saints (Symphony in the Flint Hills, 2013)
Between 1846 and 1869 thousands of Mormon immigrants traversed the Great Plains enroute to sanctuary in the Great Basin of the Rocky Mountains. The main route ran through Nebraska, paralleling the Platte River.
Keywords: Mormon; religion; cholera epidemic; Great Plains; Great Basin; Rocky Mountains; Platte River; Nebraska; settlers; pioneer; travel; west; westward; Fort Riley; Ft. Riley; Fort Kearny; Santa Fe; Oregon; The Church of Jesus Christ of Latter-day Saints